Experimental study of the dependences of retrieval efficiencies on time delay between magneto-optical-trap being turned off and optical storage - 陈力荣 徐忠孝 李萍 温亚飞 曾炜卿 武跃龙 田龙 李淑静 王海 (Chinese physics B, 2016)
We report an experimental study of electromagnetically induced transparency（EIT）-based light storage in a cloud of cold atoms loaded into a magneto-optical-trap（MOT）. After the MOT is turned off, the retrieval efficiencies of rightand left-circularly polarized signal light fields each as a function of storage time are measured for different time delays between MOT off and the storage event, respectively. The results show that in the delay ranging from 0.015 ms to 3.5 ms,the retrieval efficiency for a zero-storage time（0.2 μs） and the storage lifetime can exceed 15% and 1.4 ms, respectively.The measured results will provide important help for optimizing the storage of the polarized entanglement photons in cold atomic ensembles.